RAMAN AND INFRARED INVESTIGATIONS OF GLASS AND GLASS-CERAMICS WITH COMPOSITION 2NA(2)O-CENTER-DOT-1CAO-CENTER-DOT-3SIO(2) - Ziemath, E. C.; Aegerter, M. A. (Materials Research Society, 1994)
Precursor glass and glass-ceramics with molar composition 2Na(2)O.1CaO.3SiO(2) are studied by infrared, conventional, and microprobe Raman techniques. The Gaussian deconvoluted Raman spectrum of the glass presents bands at 625 and 660 cm(-1), attributed to bending vibrations of Si-O-Si bonds, and at 860, 920, 975, and 1030 cm(-1), attributed to symmetric stretching vibrations of SiO4 tetrahedra with 4, 3, 2, and 1 nonbridging oxygens, respectively. The Raman microprobe spectrum of a highly crystallized sample presents two narrow and intense bands at about 590 and 980 cm(-1), associated with vibrations of SiO4 tetrahedra with two nonbridging oxygens, in agreement with the predicted chain-like structure of crystalline metasilicates. Scanning electron microscopy shows that the crystals distributed in partially crystallized samples have a spherical shape, built up by radially oriented needle-like single crystals. The Raman microprobe spectra of these spherulites show that they still contain residual amorphous material. A comparison of Raman and infrared spectra of amorphous and highly crystallized samples is presented.